1995
DOI: 10.1177/026010609501000204
|View full text |Cite
|
Sign up to set email alerts
|

Old, Poor & Malnourished

Abstract: The inability of the older poor to purchase a healthy dietary cannot be solved merely by health education or budgeting skills. Primarily, they need more money.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…These two categories probably include women that were ill, and their ability to shop for food and cook is uncertain. As disability in performing these duties has been shown to cause food insecurity (Stitt et al, 1995;Wolfe et al, 1996;Wylie et al, 1999), and malnutrition is common at admittance to hospital (Larsson et al, 1990), it is problematic that this vulnerable group is often underrepresented in food surveys. In the MENEW project, study II will focus on disabled women.…”
Section: Discussionmentioning
confidence: 99%
“…These two categories probably include women that were ill, and their ability to shop for food and cook is uncertain. As disability in performing these duties has been shown to cause food insecurity (Stitt et al, 1995;Wolfe et al, 1996;Wylie et al, 1999), and malnutrition is common at admittance to hospital (Larsson et al, 1990), it is problematic that this vulnerable group is often underrepresented in food surveys. In the MENEW project, study II will focus on disabled women.…”
Section: Discussionmentioning
confidence: 99%
“…Its role is extremely important as food represents an essential component of health and wellbeing (Khan, 1981), especially for the elderly (Stitt et al, 1995). The evolution of the grocery retail industry has provided a variety of store options for contemporary shoppers in terms of size, location, product range and services; however why shoppers, and more specifically why older shoppers, choose to frequent certain stores is a question that remains unanswered.…”
Section: Shopping Motivations and Grocery Store Choicementioning
confidence: 99%
“…Although not a homogeneous group (Burt and Gabbott, 1995), low income (Stitt et al, 1995), declining health and mobility (Scottish Office, Home and Health Department 1993;Manandhar, 1995) and limited access to a car (Office for National Statistics, 1996) does describe a sub-segment of older people. Bromley and Thomas (1993), Smith (1991) and Guy (1985) have referred to older people suffering from these constraints as being marginalised and disadvantaged consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Bromley and Thomas (1993), Smith (1991) and Guy (1985) have referred to older people suffering from these constraints as being marginalised and disadvantaged consumers. Stitt et al (1995) and Henson (1992) have found this particularly to be the case with food consumers as the location of food retailers has made accessibility difficult.…”
Section: Introductionmentioning
confidence: 99%